Computer Modeling of Clot Retrieval—Circle of Willis - Phan, Thanh G.; Ma, Henry; Goyal, Mayank; Hilton, James; Sinnott, Matthew; Srikanth, Velandai; Beare, Richard (Frontiers in Neurology, 2020)
Endovascular clot retrieval (ECR), often referred to as mechanical thrombectomy (MT), has transformed the treatment of patients with ischemic stroke based on an underlying large cerebral vessel occlusion (LVO), ranging from the extracranial internal carotid artery (ICA) to the M1 (proximal) segment of the middle cerebral artery (MCA). The aim of this study was to evaluate the effect of a progressive occlusion of the extracranial portion of the ICA on the cerebral blood flow either with a conventional guiding catheter or a balloon-guiding catheter, which enables the operator to completely occlude the parent artery by inflating the balloon around the tip of this type of guiding catheter. We evaluated the impact of flow reduction in the ICA in the setting of ipsilateral MCA occlusion given the different configurations of the Circle of Willis (CoW). The computer model of cerebral arteries was based on anatomical works by Rhoton1 and van der Eecken2. The interactive experimental results are available on the web at https://gntem3.shinyapps.io/ecrsim. In the setting of left MCA occlusion, compensation from the anterior (Acom) and posterior communicating artery (Pcom) preserved the flow in the left anterior cerebral artery (ACA) but not the left MCA branches. Under selected CoW configurations such as classical, missing ACom or missing A1 segment of the ACA and concurrent right ICA occlusion, there was a progressive decrease of flow in the left ACA to a minimum of 78% when the simulated catheter fully occluded the left ICA. Flow collapsed (<10%) in the left ACA and MCA branches under CoW configurations such as bilateral fetal PCA. In summary, compensatory flow collapsed under certain clot retrieval scenarios and unusual configurations of CoW.